Short-Term Impact of FS-LASIK and SMILE on Dry Eye Metrics and Corneal Nerve Morphology. Issue 7 (July 2020) - Recchioni, Alberto; Sisó-Fuertes, Irene; Hartwig, Andreas; Hamid, Amir; Shortt, Alex John; Morris, Robert; Vaswani, Sundeep; Dermott, Jay; Cerviño, Alejandro; Wolffsohn, James Stuart; O'Donnell, Clare
Abstract : Purpose: To analyze the short-term (up to 1 month) clinical outcomes in patients undergoing corneal laser refractive surgery and the impact on dry eye disease (DED) metrics and corneal nerves using in vivo confocal microscopy (IVCM). Methods: The unaided distance visual acuity, corrected distance visual acuity, and spherical equivalent refraction (SEQ) were determined in 16 and 13 patients undergoing FS-LASIK and SMILE, respectively. DED metrics assessed were Ocular Surface Disease Index, Dry Eye Questionnaire 5-items (DEQ-5), tear film osmolarity, tear meniscus height, noninvasive keratograph breakup time (NIKBUT), ocular staining, and meibomian gland atrophy. An automated analysis of corneal nerve fiber density, corneal nerve branch density, corneal nerve fiber length (CNFL), and corneal nerve fiber fractal dimension were obtained from the IVCM scans using ACCMetrics software (University of Manchester). Results: Both surgical techniques provided good refractive and visual outcomes. DED symptoms were found to be higher after FS-LASIK compared with SMILE ( P < 0.05). A decrease in tear meniscus height (∼31%) and NIKBUT (∼40%) was reported after FS-LASIK ( P = 0.005 and P = 0.001, respectively) but not after SMILE. Both procedures affected corneal nerve fiber density, corneal nerve branch density, CNFL, and corneal nerve fiber fractal dimension, but the impact was significantly greater with FS-LASIK ( P = 0.001). Only CNFL correlated with the reported symptoms (DEQ-5) after FS-LASIK ( r = −0.545, P = 0.029). Conclusions: FS-LASIK and SMILE provided good refractive and visual outcomes. There was an increased impact on DED symptoms after FS-LASIK compared with SMILE, although there were no significant differences between the procedures for most of the other ocular surface metrics assessed. The IVCM findings showed that SMILE had less impact on corneal nerves compared with FS-LASIK.